Yahoo Web Search

  1. Is this: 2/(3 - t ) + 1/(3 + t ) + 1/(9 - t ^2) = 0? I bet it is 2 * (3 + t ) / ((3 - t ) * (3 + t )) + 1 * (3 - t ) / ((3 + t ) * (3 - t )) + 1 / (9 - t ^2) = 0 (6 + 2t) / (9 - t ^2) + (3 - t ) / (9 - t ^2) + 1 / (9 - t ^2) = 0 (6 + 2t + 3 - t + 1) / (9 - t ^2) = 0 (2t...

    1 Answers · Science & Mathematics · 23/01/2017

  2. ∫ sec^4( t /3) dt = rearrange it as: ∫ sec²( t /3) sec²( t /3) dt = ∫ sec²( t /3)[1 + tan²( t /3)] dt = expand it into: ∫ [sec²( t /3) + ...

    2 Answers · Science & Mathematics · 30/03/2009

  3. f( t ) = t ^2 - sqrt( t ) f( t +h)= ( t +h)^2 - sqrt( t +h) f( t +h)-f( t ) = ( t +h)^2 - sqrt( t +h) - t ^2 - sqrt( t ) f( t +h)-f( t ) = ( t ^2+2th+h^2) - sqrt( t +h) - t ^2 - sqrt( t ) f( t +h)-f( t ...

    1 Answers · Science & Mathematics · 27/03/2010

  4. Given r( t ) = <t², (2/3)t³, t >, note that t = 2 &lt...2). -------------- r'( t ) = <2t, 2t², 1> ==> ||r'( t )|| = √(4t² + 4t⁴ + 1) = √(2t² + 1)² = 2t²...

    1 Answers · Science & Mathematics · 21/09/2011

  5. T / T or "telegrapic transfer" is wiring money. As a.... My US bank charged me US$40 as a T / T fee. My receiving bank doesn' t charge me to receive...

    1 Answers · Business & Finance · 02/02/2007

  6. x= t cos t y=tsin t dx= (cos t -tsin t )dt dy =(sint+tcost) dt so dy/dx = (sint+tcost)/(cost-tsint...y´´ dy´/dx = =dy´/dt *dt/dx = 1/(cos t - t sin t )^2 =*[(cost-tsint)(cost+cos t -tsint )-(sin t +tcost)(-sint-sint-tcost...

    3 Answers · Science & Mathematics · 26/09/2007

  7. tan( t /2)cos^2( t ) - tan( t /2) = (sin( t /2)/cos( t /2))*cos^2( t ) - (sin( t /2)/cos( t /2)) = [sin( t /2)*cos( t /2)*cos^2( t ) - sin( t /2)*cos( t /2)]/cos^2( t /2) (using the proof, sin2t = 2sintcost) = [(1/2)sintcos^2t...

    1 Answers · Science & Mathematics · 16/02/2013

  8. T (n) - T (n-1) = log(n). T (n-1) - T (n-2) = log(n-1) T (n-2) - T (n-3) = log(n-2) T (n-3) - T (n-4) = log(n-3) ... T ...

    3 Answers · Science & Mathematics · 10/12/2006

  9. Given f( t ) = e^(-1/ t ^2) sin(1/ t ): It suffices to show that f is infinitely...1/h^2) sin(1/h) - 0] / h .......= lim(h→0) (1/h) e^(-1/h^2) sin(1/h) .......= lim( t → ±∞) t e^(- t ^2) sin t , letting t = 1/h .......= 0, since | t e^(- t ^2) sin...

    1 Answers · Science & Mathematics · 10/09/2013

  10. e^ t = 100 ln(e^ t ) = ln(100) = 4.605170186 t = 4.605170186

    1 Answers · Science & Mathematics · 07/12/2008

  1. Try asking your question on Yahoo Answers